The Law of Circumcision for Women According to the Syafi'i Mazhab, Maqashid Sharia, and Constitution - Husni Mubarok; M. Jamil; Akmaluddin Syahputera (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
The implementation of self-circumcision in Indonesia was sheltered by the government, in this case, the Ministry of Health, in 2010 with the issuance of Regulation of the Minister of Health of the Republic of Indonesia Number 1636/MENKES/PER/XI/ 2010 concerning Female Circumcision. Problems arose when the 2010 rule was repeated in 2014, resulting in discomfort among the people of Marbau District, North Labuhanbatu Regency. This study will analyze the enlightenment of the theory of legal certainty, maqashid asy-syari'ah, regarding Circumcision in the Regulation of the Minister of Health of the Republic of Indonesia Number 6 of 2014 in Marbau District, North Labuhanbatu Regency. The research method used the library (library research) and (empirical research). The Primary sources are observations, interviews, and Regulations of the Minister of Health in 2010 and 2014. The research results show that in terms of legal certainty theory, the Law is made so that it can be implemented by the community, while The 2014 repeal regulation is uncertain because it is difficult to implement. In the maqashid asy-shari'ah aspect, Circumcision is part of religious care (hifzud din), on the other hand, it does not mean that in the practice of Circumcision, harming girls or neglecting to protect oneself or one's soul (hifzhun nafs), but for the sake of giving obedience, and it is useful to control the lust of a girl when she grows up.